A study of the nature and determinants of non-disabled persons attitudes towards persons with physical disabilities and disabled persons attitudes towards their disabilities and self-acceptance as measured by the attitudes toward disabled persons scale - Riese, Edward David (Department of Sociology, 2015)
Includes bibliographical references.